PENENTUAN STRATEGIK PRIORITAS PELAYANAN LABORATORIUM KLINIK MENGGUNAKAN TEKNIK SFAS (STR ATEGIC FACT ORS ANALYSIS SUMMARY) BERSARANA ACUAN SWOT - Mulyono, B. (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
To face the global competition of clinical laboratory services, some techniques are needed for strategic formulation. SWOT, external,and internal analysis have been known as techniques for those purposes. SFAS technique was introduced recently as a simple procedureto be used as complementary tool. To evaluate an program prioritization using SFAS technique. Qualitative descriptive case analysis.Observation was done into Clinical Pathology Department of Sardjito Hospital, Yogyakarta during its activities in the year of 2006.IFA and EFA matrices showed the total scores > 2.5 and SWOT analysis revealed that the position was in 1st quadrant of the matrix.SFAS technique showed the total score > 3.0 that mean the prioritization was appropiate. SFAS technique is valuable in supportingthe formulation of strategy.